2016
DOI: 10.1097/pcc.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes in Children With Congenital Heart Disease—What Can We Impact?

Abstract: Objectives The objectives of this review are to discuss the scope of neurologic injuries in newborns with congenital heart disease, the mechanisms of injury, including pre-natal, pre- intra- and postoperative factors, neurodevelopmental outcomes and therapeutic strategies for the timely intervention and prevention of neurologic injury. Data Source MEDLINE, PubMed Conclusion At the current time, important research is underway to (1) better understand the developing brain in the fetus with complex congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
143
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(161 citation statements)
references
References 121 publications
1
143
1
2
Order By: Relevance
“…Increased hospital stay is necessary to stabilize hemodynamics and often involves lengthy exposure to sedatives which may also further impact neurodevelopment 130 . A recent study assessed operative and postoperative factors associated with poor neurodevelopmental outcomes at 13 months of age following cardiac surgery in infancy 131 .…”
Section: Risk Factors Associated With Chdmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased hospital stay is necessary to stabilize hemodynamics and often involves lengthy exposure to sedatives which may also further impact neurodevelopment 130 . A recent study assessed operative and postoperative factors associated with poor neurodevelopmental outcomes at 13 months of age following cardiac surgery in infancy 131 .…”
Section: Risk Factors Associated With Chdmentioning
confidence: 99%
“…Protracted hospital stay also exacerbates maternal and family stress and can result in an unhealthy parental-child relationship following hospital discharge as the family experiences challenges accommodating their child’s medical needs and neurodevelopmental deficits; in addition, maternal angst has a negative impact on child behavior which in turn increases maternal stress (for review, see 130 ).…”
Section: Risk Factors Associated With Chdmentioning
confidence: 99%
“…Each hour spent at an SVO2 < 40% increased the risk of abnormal neurodevelopmental outcome nearly 5‐fold. These data indirectly support the goal‐directed approach used in most pediatric CICUs …”
Section: Postoperative Carementioning
confidence: 56%
“…Both complications and LOS were included in a previously developed STS-CHSD statistical model that defined the morbidity risk associated with different surgical procedures [18]. Finally, prior studies have shown that prolonged LOS has a deleterious impact on longer term neurodevelopmental outcomes, likely reflective of LOS serving as a marker of overall postoperative morbidity [29]. The group also considered metrics associated with LOS such as duration of mechanical ventilation; however, not all STS-CHSD centers submit complete data for this variable.…”
Section: Framework and Development Of A Congenital Composite Qualitymentioning
confidence: 99%